Electric vehicle power monitoring system based on IoT sensing architecture - Jia-Syuan Lin; Zi-Fang Tsai; Zhi-Hao Wang; Hendrick (International ABEC, 2022)
At present, most of the vehicles in life are mainly based on gasoline and diesel, and with the gradual advancement of vehicle technology, but also accelerating global warming, countries have launched a variety of green energy to reduce the harm to the earth. Many vehicles have been developed into hybrid vehicles, and a large number of pure electric vehicles have been launched in recent years. On the other hand, many countries have begun to plan carbon footprint and carbon allowance management, and the emission of greenhouse gases or the use of green energy will be more regulated in the future. Therefore, this research will take the electric stacker as the test target, measure the values of current and voltage, input the measured values into the program to calculate the carbon emissions produced during operation, and obtain the carbon emissions emitted by driving electric vehicles that are significantly smaller than the carbon emissions emitted by driving gasoline and diesel vehicles.